SoTL in Malaysia higher education setting: challenges faced by new teaching scholars - Ahmad Thamrini Fadzlin Syed Mohamed,; Afifah Quraishah Abdul Nasir,; Nur Khadirah Ab. Rahman,; Emily Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Teaching is an important component in Higher Education Institutions (HEI). To ensure the quality of education in HEI, it is vital to understand the skills and duties that need to be performed by new teaching scholars. Recently, the Ministry of Higher Education has launched the Orange Book that outlines a new and proactive career track for lecturers, with the intention to develop human capital and enhance professionalism in teaching at HEI. However, there is still not much being done in identifying the challenges faced by newly appointed lecturers in Malaysia HEI. Utilising semi-structured in-depth interviews, two new teaching scholars and two expert lecturers at one of Malaysia HEI were interviewed to determine the challenges faced by new teaching scholars. Transcribed interview sessions were analysed using thematic analysis. The results show that the new teaching scholars face challenges in developing their substance knowledge, managing the Gen-Y, and having little knowledge on teaching approaches and methodologies. The paper put forward some suitable and effective suggestions in assisting these newly appointed lecturers to improve the quality of teaching and learning (T&L) process in Malaysia HEI.